Can I keep him? - Kellogg, Steven (New York : Puffin, 1976)
Mother objects to every pet Arnold asks to keep except one--a person.
Library Journal
School Library Journal
Wilson's Children
3.1
K-3
K-3
Keywords: Pets -- Fiction; Pets -- Fiction